Pengaruh Kepuasan Kerja dan Motivasi Kerja terhadap Kinerja Karyawan PT. Niti Karya Bersama - Setiawan, Lugas Aditya Diksi; Restu, Yudhi Satria (Nur Science Institute, 2022)
Employee performance refers to how employees behave in the workplace and how well they perform the job tasks that are required of them. The purpose of this study was to determine the effect of job satisfaction and work motivation on the performance of cleaning service employees. The sample in this study were 75 employees of PT. Niti Karya Bersama with sampling using purposive sampling technique. Data were collected using a scale. Data analysis using multiple regression analysis. The results of this study show that the output of Anova obtained Fcount value of 6.235 with a significance value (p) of 0.003 (p <0.05). The conclusion in this study is that there is a relationship between job satisfaction and work motivation with employee performance. Job satisfaction in the medium category, work motivation in the high category, and employee performance in the medium category. The effective contribution to the job satisfaction variable is 5.69% and the work motivation variable is 9.06%, if the two variables are added up to 14.7%, while the remaining 85.2% is influenced by other variables.